Structural basis of s54 displacement and promoter escape in bacterial transcription - Zhang,X; Gao,F; Ye,F; Zhang,B; Cronin,N; Buck,M (Proceedings of the National Academy of Sciences of USA, 2024)
Gene transcription is a fundamental cellular process carried out by RNA polymerase (RNAP). Transcription initiation is highly regulated and in bacteria, transcription initiation is mediated by sigma (σ) factors. σ recruits RNAP to the promoter DNA region, located upstream oftranscription start site (TSS), and facilitates open complex formation, where double stranded DNA is opened up into a transcription bubble and template strand DNA is positioned inside RNAP for initial RNA synthesis. During initial transcription, RNAP remains bound to sigma andupstream DNA, presumably with an enlarging transcription bubble. The release of RNAP fromupstream DNA is required for promoter escape and processive transcription elongation. Bacteria sigma factors can be broadly separated into two classes with the majority belonging to the σ70 class, represented by the σ70 that regulates housekeeping genes. σ54 forms a class on its own and regulates stress response genes. Extensive studies on σ70 have revealed the molecularmechanisms of σ70 dependent process while how σ54 transitions from initial transcription to elongation is currently unknown. Here we present a series of cryo electron microscopy structures of the RNAP-σ54 initial transcribing complexes with progressively longer RNA, which reveal structural changes that lead to promoter escape. Our data show that initially, the transcription bubble enlarges, DNA strands scrunch, reducing the interactions between σ54 and DNA strands in the transcription bubble. RNA extension and further DNA scrunching help to release RNAP from σ54 and upstream DNA, enabling the transition to elongation.